DISTRIBUIÇÃO DE MASSA SECA E RENDIMENTO DE FEIJÃO-CAUPI INOCULADAS COM RIZÓBIO EM GURUPI, TO - PAULO ROGÉRIO SIRIANO BORGES; RITA DE CÁSSIA CUNHA SABOYA; LUCIANO MARCELO FALLÉ SABOYA; ELONHA RODRIGUES DOS SANTOS; SHARA EMANUELLA ALVES DE SOUZA (Revista Caatinga, 2012)
The aim of this paper was to evaluate the contribution of different strains of rhizobia in the distribution of dry material and grain yield in cowpea plants, grown in cerrado in the state of Tocantins. The experiment was conducted in 2007/2008 season in cerrado in Gurupi, TO. Five treatments were studied with strains BR3301, BR3302, BR3267, BR3299 and BR3262 and treatment as a control (no inoculation and fertilizer). Plants were collected at 15, 25, 35, 45, 55 and 65 days after emergence (DAE) to determine the distribution of dry mass of leaves, stems, flowers and pods and the weight ratio of plant parts. Grain yield was determined at harvest as grain moisture reached 13%. We established the Pearson correlation coefficient of variables. The witness and BR3299 treatments promoted greater dry mass of plants at 65 DAE. The highest yield was obtained by the witness and BR3267. Further study is needed on the selection of strains of nitrogen-fixing bacteria in cowpea under various soil and climate in the state of Tocantins.